The effect of deficient muscarinic signaling on commonly reported biochemical effects in schizophrenia and convergence with genetic susceptibility loci in explaining symptom dimensions of psychosis - Vakalopoulos, Costa (Frontiers in Pharmacology, 2014)
With the advent of DSM 5 criticism has generally centred on a lack of biological validity of the diagnostic criteria. Part of the problem in describing a nosology of psychosis is the tacit assumption of multiple genetic causes each with an incremental loading on the clinical picture that fails to differentiate a clear underlying pathophysiology of high impact. The aim of this paper is to consolidate a primary theory of deficient muscarinic signalling underlying key clinical features of schizophrenia and its regulation by several important genetic associations including neuregulin, DISC and dysbindin. Secondary reductions in markers for GABAergic function and changes in the levels of interneuron calcium binding proteins parvalbumin and calbindin can be attributed to dysfunctional muscarinic transduction. A parallel association exists for cytokine production. The convergent pathway hypothesis is likewise used to model dopaminergic and glutamatergic theories of schizophrenia. The negative symptom dimension is correlated with dysfunction of Akt and ERK transduction, a major point of convergence. The present paradigm predicts the importance of a recent finding of a deletion in a copy number variant of PLCB1 and its potential use if replicated, as one of the first testable biological markers differentiating schizophrenia from bipolar disorder and further subtyping of schizophrenia into deficit and non-deficit. Potential limitations of PLCB1 as a prospective marker are also discussed.